1998
DOI: 10.1093/carcin/19.1.147
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of hydrazines-derived alkyl radicals to cytotoxicity and transformation induced in normal c-myc-overexpressing mouse fibroblasts

Abstract: Several hydrazine derivatives (HD) tested so far have pharmacological activities, but many also have toxic side effects, including carcinogenesis. Their toxicity has been ascribed to carbocations (via formation of azoxy intermediates), alkyl radicals or reactive oxygen species. Cytotoxicity and transformation by carbocations is widely accepted, but the role of alkyl radicals is still questioned. We have investigated the cytotoxicity of HD to mouse fibroblasts in three activation systems in which enhanced alkyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…Metabolic studies performed with monosubstituted derivatives support the route shown in Fig. (14) [203][204][205].…”
Section: Hydrazines 8 Vinca Alkaloidsmentioning
confidence: 57%
See 1 more Smart Citation
“…Metabolic studies performed with monosubstituted derivatives support the route shown in Fig. (14) [203][204][205].…”
Section: Hydrazines 8 Vinca Alkaloidsmentioning
confidence: 57%
“…This sequence bears analogy to that described in the Peroxides section. Alternatively, evidence exists for a DNA alkylating pathway [204].…”
Section: Hydrazines 8 Vinca Alkaloidsmentioning
confidence: 99%
“…Several studies revealed that AOM is a potent carcinogen for the liver (Chastre et al 2012) and at low doses induce hepatotoxicity with ductular hyperplasia (Shan et al 2008;Khurana et al 2010). Although derived from a rare plant and human exposure to AOM is infrequent, exposure to structurally related hydrazine compounds that are found in herbicides, rocket fuels, tobacco and drugs is common (Gamberini et al 1998). Therefore, by use of AOM-induced hepatic injury in mice we conducted the present study to elucidate the role of brown seaweeds in mitigating AOM-induced hepatotoxicity.…”
Section: Effect Of T Ornata and P Pavonia On Liver Nf-jb And Pparc mentioning
confidence: 99%
“…Hydrazine derivatives are activated to reactive intermediates, such as free radicals and carbocations, through a variety of cellular oxidative metabolic pathways. Aliphatic azo and azoxy species are intermediates in the activation pathways of hydrazine [15].…”
Section: Us Epa's Oncologic R Expert System and Modulating Factors Fomentioning
confidence: 99%